Calcium phosphate-based nanomedicine mediated CRISPR/Cas9 delivery for prostate cancer therapy - Wei, Chao-Gang; Zhang, Rui; Wei, Lan-Yi; Pan, Peng; Zu, He; Liu, Ya-Zhen; Wang, Yong; Shen, Jun-Kang (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Erythropoietin producing hepatocyte receptor A2 (EphA2) is widely presented in the tumor cells, closely related to tumor cell migration, not cell apoptosis and proliferation. Based on its high expression in castration-resistant prostate cancer (CRPC), we herein develop a CRISPR-Cas9-based genome-editing nanomedicine to target erythropoietin producing hepatocyte receptor A2 for the treatment of castration-resistant prostate cancer. Methods: To this end, TAT was designed to stabilize the distribution of calcium, and then bound to ribonucleoprotein (RNP) to form nanoparticles RNP@CaP-TAT. Results: This nanoparticle has a simple synthesis process with good biocompatible, to achieve the knockout of tumor cells (PC-3) targeting erythropoietin producing hepatocyte receptor A2 gene and to effectively suppress the migration of tumor cells. Discussion: This delivery genome editing system provides a promising gene therapy strategy for the treatment of castration-resistant prostate cancer, showing good potential against castration-resistant prostate cancer tumor metastasis. In addition, it can be extended to other types of cancer with highly heterogeneous gene expression.